2008
DOI: 10.1007/s00464-008-0119-2
|View full text |Cite
|
Sign up to set email alerts
|

Low-pressure pneumoperitoneum versus standard pneumoperitoneum in laparoscopic cholecystectomy, a prospective randomized clinical trial

Abstract: Low-pressure pneumoperitoneum tended to be better than standard-pressure pneumoperitoneum in terms of lower incidence of shoulder tip pain, but this difference did not reach statistical significance following elective laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
95
4
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 24 publications
6
95
4
4
Order By: Relevance
“…The use of pharmacological agents to achieve deep relaxation throughout the laparoscopic procedure allows the surgeons either to proceed at the same level of CO 2 insufflation while benefitting from better surgical conditions, or lowering the insufflating pressure to lower the risk of surgical complications. Several studies have shown the positive effect of lowering the working pressure 5,6,7 . One symptom that is often seen after laparoscopic hysterectomies is shoulder pain, which is often stated as a major problem and the most important issue when speaking to the patient at follow up.…”
Section: Introductionmentioning
confidence: 99%
“…The use of pharmacological agents to achieve deep relaxation throughout the laparoscopic procedure allows the surgeons either to proceed at the same level of CO 2 insufflation while benefitting from better surgical conditions, or lowering the insufflating pressure to lower the risk of surgical complications. Several studies have shown the positive effect of lowering the working pressure 5,6,7 . One symptom that is often seen after laparoscopic hysterectomies is shoulder pain, which is often stated as a major problem and the most important issue when speaking to the patient at follow up.…”
Section: Introductionmentioning
confidence: 99%
“…Various authors have reported that laparoscopic cholecystectomy performed with LPP results in a better postoperative quality of life as compared to laparoscopic cholecystectomy performed with HPP. [16][17][18] In our study contact of parietal peritoneum to the underlying viscera during secondary port insertion under vision after insertion of primary port, was taken as indirect indicator of potential of causing visceral injury at a particular intraabdominal pressure. Out of 180 secondary ports inserted, there was evident contact of 20 (11.1%) secondary ports in high pressure groups and 14 (7.7%) secondary ports in low pressure group, which is suggestive of adequate exposure and working space available for surgery at both pressures.…”
Section: Discussionmentioning
confidence: 99%
“…En seres humanos y animales, la laparoscopia causa malestar en los pacientes (16,18). El origen del dolor post-laparoscopia en humanos se puede clasificar en tres aspectos: visceral, incisión y dolor en el hombro (este último asociado posiblemente a la sobredistensión de las fibras musculares del diafragma) (18).…”
Section: Discussionunclassified
“…El origen del dolor post-laparoscopia en humanos se puede clasificar en tres aspectos: visceral, incisión y dolor en el hombro (este último asociado posiblemente a la sobredistensión de las fibras musculares del diafragma) (18). Los trabajos realizados en caninos, demuestran la reducción en el dolor comparado con las técnicas abiertas; sin embargo no se conocen trabajos que identifiquen dolor visceral o de otro tipo asociado al pneumoperitoneo.…”
Section: Discussionunclassified